The Roles of Organizational Commitment in Mediating the Effects of Big Five Personality on Worker’s Adherence to Occupational Safety SOPs - Hadi Prayitno; Tjipto Suwandi; Hamidah Hamidah (Institute of Advanced Engineering and Science, 2016)
The incidence of work accidents in the construction industry particularly in Indonesia and generally in international shows an increasingly worrying trend given that either quantitatively or qualitatively the number of work accidents is very large compared to that of other industrial sectors. The main causing factors are mostly due to the workers’ behavior. This study aimed to determine the roles of organizational commitment in mediating the effects of Big Five Personality on workers’ adherence to occupational safety SOPs. The study belongs to observational analytic type with cross sectional study design. The study involved 140 samples taken randomly from workers at manufacturing department of PT. Boma Bisma Indra Pasuruan, East Java. The measurement of personality used five factor model (FFM) questionnaire of Costa & McRae. Hypothesis testing applied inferential statistical analysis. The statistical method used was Structural Equation Model (SEM). The results showed that Organizational Commitment had lower roles in mediating the effects of Big Five Personality on workers’ adherence to occupational safety SOPs compared to that Big Five Personality in directly influencing the workers’ adherence to occupational safety SOPs at PT. Boma Bisma Indra Pasuruan.